Peningkatan Kemampuan Pemecahan Masalah Melalui Model Problem Based Learning - Ayu Setyawati; Nila Kesumawati; Dessy Atikah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study is to improve the creative thinking ability of class X TITL 1 students of SMk Negeri 1 South Indralaya through the application of problem-based learning models. This study used a class action research method in two action cycles. The data collection techniques used are tests and observations. This class action research has 4 stages that must be met, namely planning, implementation, observation and reflection. The research subjects in this study were students of class X TITL 1 students of SMK Negeri 1 South Indralaya total of 35 students consisting of 20 men and 15 women. From the results of the study showed that the value of student’s problem solving skills increased, this can be seen in the completion of student learning in the first cycle, the average score of students in problem solving skills was 61.21% with the category of enough, then in cycle II the average score of student’s problem solving was 82.37%. This is supported by the results of observations, student activity has increased, in cycle I the percentage of student activity reached a total score of 193 with a percentage of 68.93%, cycle II increased to a total score of 231 with a percentage of 82.50%. So, it can be concluded that by showing that the Problem Based Learning learning model can also increase student learning activities in problem solving and learning activities of class X TITL 1 students of SMK Negeri 1 South Indralaya Keywords: Problem Based Learning, Problem Solving Skill